Experiencia física del servicio y su relación con el posicionamiento y manejo de fauna en el Complejo Turístico de Quistococha en Iquitos, año 2019 - Rodríguez Pinedo, Sergio Enoc (2021)
The objective of this research was to determine the relationship between the physical experiences of the service with the positioning and management of fauna in the Quistococha Tourist Complex in Iquitos year 2019, the methodology used was descriptive, quantitative - correlational, and The size of the sample was calculated through the formula of finite populations, with a total of 365 visitors surveyed, having as the first study variable the physical experience of the service, the second variable the positioning and the third variable the management of fauna, but from a user perception, in the results it was observed that the category of physical experience of the service by visitors is good in 95.1%, in the category of positioning, a high level of positioning of the Tourist Complex was also observed. Quistococha in visitors with 94%, and the category of fauna management, according to the perception of the visitors, an adequate management was observed in 87.4% that to determine the degree of relationship the chi square was used with a level of significance of 0.05%, where it was determined that if there is a relationship between the variable of physical experience of the service of the Complex Tourism of Quistococha with the positioning, with a significance value of 0.000, therefore the hypothesis is accepted, however, no relationship was found between the physical experience of the service with the management of fauna, having a significance value of 0.632, for Therefore, the hypothesis is rejected.